Elements of Punishment and Prisoner Development in Narcotics Crime (Study on the Development of Prisoners in Correctional Institution Class IIA Pancur Batu Deli Serdang Regency) - Agam Saputra Antonius; Yasmirah M.S.; T.Riza Zarzani (LAWYER: Jurnal Hukum, 2023)
This study aims to look at the Criminal Elements and Prisoner Development in Narcotics Crimes (Study of Prisoner Development at Klas IIA Pancur batu Correctional Institution, Deli Serdang Regency. This type of research is a descriptive research method with qualitative methods and a Juridical Sociological approach (social legal approach). The result of this research is that the Correctional System can be achieved, namely forming Prisoners to become fully human, realize their mistakes, improve themselves, and also not repeat criminal acts so that they can be accepted back by the community environment, play an active role in development and live reasonably as good and responsible citizens. Inmate Development Patterns, consisting of Personality Development and Independence Development.